Safety Management Systems Implementation : A Study Utilizing In The Grounded Theory Analysis - Othman, Norfaridatul Akmaliah; Jabar, Juhaini; Sallehuddin, Nur Syazwani; Kamarudin, Mohd Fauzi (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2014)
-